2014
DOI: 10.1016/j.neuroscience.2014.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the addiction cycle: A complex biology with distinct contributions of genotype vs. sex at each stage

Abstract: Ethanol abuse can lead to addiction, brain damage and premature death. The cycle of alcohol addiction has been described as a composite consisting of three stages: intoxication, withdrawal and craving/abstinence. There is evidence for contributions of both genotype and sex to alcoholism, but an understanding of the biological underpinnings is limited. Utilizing both sexes of genetic animal models with highly divergent alcohol withdrawal severity, Withdrawal Seizure-Resistant (WSR) and Withdrawal Seizure-Prone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 107 publications
(153 reference statements)
6
54
0
Order By: Relevance
“…In light of this, particularly intriguing was a gene expression profile approach to the study of withdrawal seizure-prone and withdrawal seizureresistant mice. A prominent common gene regulatory node in the medial prefrontal cortex that was activated during acute withdrawal for both sexes was the nuclear factor kB transcription factor, but the immune response was dramatically sexually dimorphic, with females presenting a proinflammatory gene expression profile and males presenting an anti-inflammatory gene expression profile (Wilhelm et al, 2014). The authors suggested that each stage of the addiction cycle is differentially influenced by sex versus genetic background, and they argued for the development of stageand sex-specific therapies for alcohol withdrawal and relapse prevention.…”
Section: Sex Differences In Addictionmentioning
confidence: 99%
“…In light of this, particularly intriguing was a gene expression profile approach to the study of withdrawal seizure-prone and withdrawal seizureresistant mice. A prominent common gene regulatory node in the medial prefrontal cortex that was activated during acute withdrawal for both sexes was the nuclear factor kB transcription factor, but the immune response was dramatically sexually dimorphic, with females presenting a proinflammatory gene expression profile and males presenting an anti-inflammatory gene expression profile (Wilhelm et al, 2014). The authors suggested that each stage of the addiction cycle is differentially influenced by sex versus genetic background, and they argued for the development of stageand sex-specific therapies for alcohol withdrawal and relapse prevention.…”
Section: Sex Differences In Addictionmentioning
confidence: 99%
“…Mice were exposed to ethanol continuously for 72 h in vapor inhalation chambers as previously described (44,119). This paradigm has been characterized as a vulnerability model [see (119)], with a single chronic exposure to high intoxication, followed by synchronized withdrawal.…”
Section: Chronic Ethanol Exposurementioning
confidence: 99%
“…Nevertheless, increased vulnerability to EtOH-induced neurotoxicity in females remains controversial [reviewed in (51)] with additional studies needed to support or refute this hypothesis. This finding is buttressed by the observation that chronic ethanol exposure is associated with a strongly sexually dimorphic transcriptional response (44,118,119). In those studies, significantly regulated transcripts included several genes that are exclusively or predominantly expressed in astrocytes, suggesting that a component of the neuroadapative response in the brain after ethanol exposure reflects changes in astrocyte gene expression that are distinct between males and females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, pursuing general NIH program interest in male-female differences, we considered how parameter estimates might differ for male and female drug users (Mello N.K., 1986;Sartor et al, 2014;Wagner and Anthony, 2007;Wetherington, 2007;Wilhelm et al, 2014). In prior work, female-male contrasts for risk of becoming dependent assume that age is held constant (e.g., Chen and Kandel, 2002) or hold constant elapsed time since first onset of drug use (e.g., Sartor et al, 2014;Wagner and Anthony, 2007).…”
mentioning
confidence: 99%